Jim Crow : a historical encyclopedia of the American mosaic - Brown, Nikki L. M.; Stentiford, Barry M. (Gale virtual reference library., 2014)
This one-volume reference work examines a broad range of topics related to the establishment, maintenance, and eventual dismantling of the discriminatory system known as Jim Crow." rovides a one-stop source of information for students researching the period of American history dominated by the discriminatory system of Jim Crow laws " uts phenomena such as 'Sundown towns' within a larger framework of official discrimination " ocuments the methods used to create, maintain, and dismantle Jim Crow.